Pengaruh Kualitas Produk, Harga, dan Citra Merek terhadap Minat Beli Kembali dengan Kepuasan Konsumen sebagai Variabel Mediasi pada Produk Uniqlo - Saputa, I Putu Agus; Mahyuni, Luh Putu; Mandira, I Made Candra; Sari, Desak Made Febri Purnama (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study analyzes how product quality, price, and brand image influence repurchase intention, with consumer satisfaction acting as a mediating variable in the context of Uniqlo products. Competition in Indonesia’s fashion retail sector has intensified, especially among Generation Z consumers who are highly responsive to value perception and brand experience. Understanding the drivers that shape their repurchase behavior is therefore essential. Data were obtained through an online survey completed by 189 respondents selected using purposive sampling. The analysis employed Partial Least Squares (PLS) through SmartPLS 4 to assess both measurement and structural models. The results indicate that product quality, price fairness, and brand image each contribute positively to consumer satisfaction. Furthermore, consumer satisfaction and product quality significantly strengthen repurchase intention. Brand image shows both a direct effect on repurchase intention and an indirect influence through consumer satisfaction as a mediating factor. The model also demonstrates strong predictive relevance, highlighting the importance of these variables in explaining repeat purchasing behavior. These findings reinforce the role of perceived value and brand credibility in maintaining consumer loyalty within the competitive fashion retail landscape.